2022
DOI: 10.3389/fneur.2021.798264
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Catatonic Stupor in Behavioral Variant Frontotemporal Dementia

Abstract: Catatonia is a psychomotor syndrome common to several medical and neuropsychiatric disorders. Here, we report on the case of a 95-year-old woman who underwent a radical change in personality characterized by sexual disinhibition, and physical and verbal aggressiveness. Over several months, she developed verbal stereotypies, gait deterioration, and double incontinence. She eventually developed mutism and an active opposition to all attempts to be fed or cared for. Benzodiazepines, olanzapine and electroconvulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Furthermore, in Grant an Mohan 23 study, the worsening of cognition was debatable and could be attributed to the severe stage of dementia per se. Nevertheless, in most studies, cognition was not reported, and due to agitation and behavioral disturbances, among others, a standardized cognitive assessment was not available [14][15][16]22,24,26,27,29,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Grant an Mohan 23 study, the worsening of cognition was debatable and could be attributed to the severe stage of dementia per se. Nevertheless, in most studies, cognition was not reported, and due to agitation and behavioral disturbances, among others, a standardized cognitive assessment was not available [14][15][16]22,24,26,27,29,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients underwent ECT since they did not respond sufficiently to psychopharmacological treatment. In 9 reports the ECT leads were placed bilaterally -bifrontal or bitemporal 11,15,16,[23][24][25][26][27][28][29] -followed by right unilateral ECT in 2 reports 30,31 . Two publications did not disclose the lead placement 32,33 .…”
Section: Case Reportsmentioning
confidence: 99%